Biokinetics of Plutonium in Nonhuman Primates. Issue 4 (October 2016) - Poudel, Deepesh; Guilmette, Raymond A.; Gesell, Thomas F.; Harris, Jason T.; Brey, Richard R.
Abstract : Abstract: A major source of data on metabolism, excretion and retention of plutonium comes from experimental animal studies. Although old world monkeys are one of the closest living relatives to humans, certain physiological differences do exist between these nonhuman primates and humans. The objective of this paper was to describe the metabolism of plutonium in nonhuman primates using the bioassay and retention data obtained from macaque monkeys injected with plutonium citrate. A biokinetic model for nonhuman primates was developed by adapting the basic model structure and adapting the transfer rates described for metabolism of plutonium in adult humans. Significant changes to the parameters were necessary to explain the shorter retention of plutonium in liver and skeleton of the nonhuman primates, differences in liver to bone partitioning ratio, and significantly higher excretion of plutonium in feces compared to that in humans.